A hyperacute immune map of ischaemic stroke patients reveals alterations to circulating innate and adaptive cells. (9th December 2020) - Krishnan, S.; O'Boyle, C.; Smith, C. J.; Hulme, S.; Allan, S. M.; Grainger, J. R.; Lawrence, C. B.
Summary: Systemic immune changes following ischaemic stroke are associated with increased susceptibility to infection and poor patient outcome due to their role in exacerbating the ischaemic injury and long‐term disability. Alterations to the abundance or function of almost all components of the immune system post‐stroke have been identified, including lymphocytes, monocytes and granulocytes. However, subsequent infections have often confounded the identification of stroke‐specific effects. Global understanding of very early changes to systemic immunity is critical to identify immune targets to improve clinical outcome. To this end, we performed a small, prospective, observational study in stroke patients with immunophenotyping at a hyperacute time point (< 3 h) to explore early changes to circulating immune cells. We report, for the first time, decreased frequencies of type 1 conventional dendritic cells (cDC1), haematopoietic stem and progenitor cells (HSPCs), unswitched memory B cells and terminally differentiated effector memory T cells re‐expressing CD45RA (TEMRA). We also observed concomitant alterations to human leucocyte antigen D‐related (HLA‐DR), CD64 and CD14 expression in distinct myeloid subsets and a rapid activation of CD4 + T cells based on CD69 expression. The CD69 + CD4 + T cell phenotype inversely correlated with stroke severity and was associated with naive and central memory T (TCM) cells. Our findings highlight early changes in both the innate and adaptive immune compartments for further investigation as they could have implications the development of post‐stroke infection and poorer patient outcomes. Abstract : Stroke affects millions of people across the globe and infections following a stroke often lead to death or disability in patients. Looking rapidly after a stroke in patients, we identify early alterations to the innate and adaptive cells in circulation. Our findings highlight novel changes to dendritic cells, monocytes, haematopoietic stem and progenitor cells, B and T cells to be further investigated as they could have implications the development of post‐stroke infection and poorer patient outcomes.